Eco-Tourism in the Chepang Hill Trail in Nepal - Dhakal, Chandra Prasad (Interdisciplinary Journal of Management and Social Sciences, 2023)
The Chepang hill trail is one of the important hill trails of Nepal. It is located in Dhading and Chepang district. The study analyzes situations and impacts of the trail in eco- tourism.  Eco-tourism brings social, economic and cultural changes in the study area through promoting business, enhancing infrastructure, however, waste management, sanitation problem is going to increasing due to tourism and overall ecosystem and eco-tourism will face problem in future. In this context the study concentrated on the situation and impacts of ecotourism in the surrounding area of the Chepang hill trail. Main objective of this study is to analyze the respondents' perception on the situation and impact. The study followed quantitative and qualitative research design and analyzed the issue by using both primary and secondary source of data. Primary data were collected from the field study. Interview schedule and observation checklist was used to collect information from the field and collected information was managed through paragraph description and tabulation. On the basis of data interpretation, it is found that respondents have neither bad nor excellent perception about the impacts eco-tourism in study area.